Influence of institutional distance on cross-border mergers and acquisitions in Latin America - Thai Hieu, Phan (My University, 2026)
Cross-border mergers and acquisitions (M&As) serve as a key mechanism for firms to achieve rapid internationalization, access new markets, and acquire strategic resources. However, their success is heavily influenced by institutional distance factors (IDFs), the differences in formal institutions and informal institutions between home and host countries. While M&A research has predominantly examined developed economies and Asian emerging markets such as China and India, Latin America remains relatively underexplored. This gap is particularly notable amid the region’s rising M&A activity, nearshoring trends, natural resource abundance, and recent trade advancements like the EU-Mercosur agreement. This thesis addresses the research question: How are institutional distance factors in emerging markets, with a focus on Latin America, influencing cross-border M&A processes? Adopting an interpretivist philosophy and an inductive qualitative approach, the study relies on secondary data consisting of industry reports, alongside expert videos and podcasts featuring practitioners with extensive Latin American M&A experience. The data were analyzed using the Gioia methodology, progressing systematically from initial codes to first- and second-order themes, and ultimately to aggregate dimensions. The analysis uncovers three core aggregate dimensions through which institutional distance factors shape CBMA processes: (1) interpreting institutional context for strategic market selection; (2) strategically managing risk–reward trade-offs in market entry; and (3) building institutional capabilities for deal execution and integration. These findings are integrated into a novel processual framework of institutional distance in M&As, illustrating how formal and informal IDFs dynamically influence the pre-deal, deal-making, and post-deal phases while underscoring the central role of capability development and knowledge transfer. Theoretically, the study extends institutional theory and M&A literature by providing a Latin American regional lens and addressing inconsistencies in prior findings. Managerially, it offers practical guidance for executives and investors on navigating Latin American institutional complexities through local expertise and adaptive strategies. Societally, it fosters a more nuanced understanding of the region’s institutional diversity and supports policies aimed at attracting quality foreign investment and promoting sustainable economic development.
Keywords: institutions (social mechanisms); institutions (formal organisation); distances; mergers; acquisition; corporate acquisitions; foreign investments; international corporations; internationalisation; international trade; Latin Americans; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development